Оптимізація схеми зняття показників резистивних сенсорів, мінімізація споживання струму - Левченко, Є. В. (ХНУРЕ, 2021)
This article presents an approach developed for collecting and processing data about the current stress state of a structural component of a technical product and to estimate its residual fatigue life in case of random dynamic loadings. As input data sensor values are being used from which the operating loads acting on a component are calculated.
Keywords: схемА зняття показників; резистивниЙ сенсор